The social process of knowledge creation in science - Love, Hannah Beth, author; Cross, Jennifer E., advisor; Fosdick, Bailey K., committee member; Nowacki, Jeffrey, committee member; Carolan, Michael, committee member (Colorado State University. Libraries, 2019)
The Science of Team Science (SciTS) emerged as a field of study because 21st Century scientists are increasingly charged with solving complex societal and environmental challenges. This shift in the complexity of questions requires a shift in how knowledge is created. To solve the complex societal health and environmental challenges, scientific disciplines will have to work together, innovate new knowledge, and create new solutions. It is impossible for one person or one discipline to have the quantity of knowledge needed to solve these types of problems. Tackling these problems requires a team. My dissertation articles report on how knowledge is built and created on a spectrum of scientific teams from university students to long-standing teams. Collectively they answer: how is knowledge creation a social process? To answer this question, my dissertation used a mixed-methods approach that included: social network analysis, social surveys, participant observation, interviews, document analysis, and student reflections. The most important finding from my dissertation was that social relations and processes are key to knowledge creation. Historically, knowledge acquisition and creation have been thought of as individual tasks, but a growing body of literature has framed knowledge creation as a social product. This is a fundamental shift in how knowledge is created to solve complex problems. To work with scientists from other disciplines, individuals must develop personal mastery and build the necessary capacities for collaboration, collective cognitive responsibility, and knowledge building. Complex problems are solved when scientists co-evolve with teams, and individual knowledge and capacity grows alongside the ability for "team learning" Knowledge, then, is a collective product; it is not isolated or individual, but constructed and co-constructed through patterns of interactions.
Keywords: mixed methods; social network analysis; knowledge creation; team science; science of team science (SciTS)